Intravacuolar persistence in neutrophils facilitates Listeria monocytogenes spread to co-cultured cells - Stefano Bagatella; Camille Monney; Natascha Gross; Véronique Bernier Gosselin; Gertraud Schüpbach-Regula; Andrew Hemphill; Anna Oevermann (mBio)
ABSTRACT The bacterium Listeria monocytogenes (Lm) causes listeriosis in humans and ruminants. Acute lesions are predominantly infiltrated by polymorphonuclear neutrophils (PMNs), considered to be the efficient bactericidal arm of innate immunity. However, recent evidence suggests that PMNs cannot achieve antilisterial sterilizing immunity and that Lm may persist within PMNs. Despite this, interactions between PMNs and Lm remain poorly understood. In this study, we characterized the listericidal activity and interaction dynamics of bovine PMNs with Lm ex vivo. Phagocytosed Lm failed to escape into the PMN cytosol and was primarily targeted by phagolysosomal mechanisms. However, PMNs enabled prolonged intravacuolar survival of a resilient Lm subpopulation, largely as viable but non-culturable (VBNC) bacteria. This resilient Lm population could spread from PMNs to a cell line, resuscitate, and complete its canonical life cycle, thereby perpetuating the infection. Therefore, we identify PMNs as a mobile niche for Lm survival and provide evidence that PMNs harbor VBNC bacteria, potentially facilitating Lm dissemination within the host.IMPORTANCEListeria monocytogenes (Lm) is a significant foodborne pathogen responsible for high hospitalization rates in humans, especially vulnerable groups such as the elderly, pregnant women, and immunocompromised individuals. In animals like ruminants, Lm infection leads to severe disease manifestations, notably brainstem encephalitis. This study uncovers a novel mechanism by which bovine neutrophils (PMNs) harbor Lm in a viable but non-culturable (VBNC) state, enabling the bacteria to hide in the host. PMNs, traditionally viewed as bacteria killers, may serve as Trojan horses, allowing Lm to persist and spread within the host. This discovery has broad implications for understanding Lm's persistence, its role in recurrent infections, and the development of new therapeutic strategies targeting VBNC forms of Lm to improve treatment outcomes and disease control.